2013
DOI: 10.1136/bmjopen-2012-001541
|View full text |Cite|
|
Sign up to set email alerts
|

The clinical implications of elevated blood metal ion concentrations in asymptomatic patients with MoM hip resurfacings: a cohort study

Abstract: ObjectiveTo determine whether elevated blood cobalt (Co) concentrations are associated with early failure of metal-on-metal (MoM) hip resurfacings secondary to adverse reaction to metal debris (ARMD).DesignCohort study.SettingSingle centre orthopaedic unit.ParticipantsFollowing the identification of complications potentially related to metal wear debris, a blood metal ion screening programme was instigated at our unit in 2007 for all patients with Articular Surface Replacement (ASR) and Birmingham MoM hip resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 31 publications
0
47
3
1
Order By: Relevance
“…In patients who had bilateral arthroplasties, only HHS and cobalt levels remained significant predictors of revision surgery. These findings are partly consistent with those of some studies which have found elevated blood cobalt concentrations to be a risk factor for joint failure [10,17]. Our findings, however, deviate from those of the aforementioned studies identifying female sex as an independent predictor of revision surgery.…”
Section: Discussioncontrasting
confidence: 54%
“…In patients who had bilateral arthroplasties, only HHS and cobalt levels remained significant predictors of revision surgery. These findings are partly consistent with those of some studies which have found elevated blood cobalt concentrations to be a risk factor for joint failure [10,17]. Our findings, however, deviate from those of the aforementioned studies identifying female sex as an independent predictor of revision surgery.…”
Section: Discussioncontrasting
confidence: 54%
“…When specifically evaluating rates of ALTR between genders, our data demonstrated an increased rate of complication in women; however, a paucity of data specifically evaluating this finding exists [4,5,11,23]. With the available evidence, conclusions are limited as to the cause of our observed findings.…”
Section: Discussionmentioning
confidence: 69%
“…Another change in modern trunnion design in that most tend to have a ridge surface machined into the material to accommodate ceramic heads. As shown by Langton et al [4] and Hexter et al [18] , these grooves leave imprints on the majority of tapers and thus increase wear rate and material loss. This could also lead to increased corrosion.…”
Section: Has the Design Of Modern Pros-theses Changed And Does This Hmentioning
confidence: 99%
“…The term adverse reaction to metal debris (ARMD) is an umbrella term that has been used to describe the effects of metal ion deposition within soft tissues in the body. Patients who become symptomatic and develop ARMD frequently need revision of their prostheses [3] , whilst those who are asymptomatic but suffer with high serum metal ion levels represent a more controversial group to treat [4] .…”
Section: Introductionmentioning
confidence: 99%